TUBERCOLOSIS PROGRAM EVALUATION WITH STRATEGY OF DOSTS IN EAST JAVA PROVINCE ON 2009 – 2013 - Nur Haidah; Darjati .; Ferry K; Khambali . (Poltekkes Kemenkes Surabaya, 2016)
Tuberculosis (TB) is still a public health problem that is becoming a global challenge. Indddonesia is the first country among the countries with a high TB burden in the Southeast Asia region which managed tohit the target for Global TB on 2006. The strategy of the Direct Observed Treatment Shotcourse (DOTS) have managed to achieve two goals that helped were declared the World Health Assembly (WHA) on 1991, that the detection of new cases of BTA positive 70 %, and the healing of 85 % of the cases in 2000. An important aspect in Pulmonary TB is a countermeasure to support monitoring and evaluation that are appropriate and correct. This study aims to evaluate the achievement of program control with TB DOTS strategy in direct region of East Java Province on 2009 – 2013.This research is deskriptip to describe and evaluate the program for tackling pulmonary tuberculosis with DOTS strategy in East Java Province. Data collection was carried out through a questionnaire to the program manager (Wasor) and data from reports of TB program execution for five years (2009 – 2013) which are then processed in diskriptif.The process of implementation of the programme of TB in East Java Propince all kabupaten/kota have been referred to the National TB guidelines, but figures close to indicators for each district region haven’t all reached in accordance with the targets that have been set. Among other networkong suspek 86,8 % number of district region have yet to reach the target, the discovery of a case of 63,2 % district region heve yet to reach the target.In order to improve TB Program indicator close to the recommended extension for empowereng community perpetrated, TB program manager commitment required corresponding mapping TB cases at least up yo the village level, the strengthening of the system and the participation of allmprofessionals/health service by means of : private sector obligations (doctor, hospital, clinic) to examine, diagnose and treat patients with TB standars procedure DOTS. Keywords : Evaluation, tubercolusis, DOTS.